The Politics of Religion in Sisworo Gautama Putra’s and Joko Anwar’s Pengabdi Setan - Anton Sutandio (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2019)
This research compares two films, the original Pengabdi Setan and its remake, in the context of politics of religion to show how the two films depict the issue of religion at two different eras based on the released years of the two films. The display of religion in the two films is viewed as an allegorical representation as well as critical responses to the socio-political situation of the two eras. Separated by almost four decades, Joko Anwar’s nostalgic remake and the original film subtly converse with each other, share distinctive similarities yet also polarized differences that underlie their endeavor to allegorically bring back and relive public memory of certain national trauma; that is repression during the New Order regime and marginalization of the minority in contemporary Indonesia. By focusing on the films’ cinematography and mise-en-scene, this research attempts to locate those allegorical moments within the depiction of religious practice that challenge, criticize or accentuate the dominant ideology of their respective eras. Keywords: allegorical moment, religion, national trauma, politicization